2018
DOI: 10.17126/joralres.2017.089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sonic versus ultrasonic activation on aqueous solution penetration in root canal dentin.

Abstract: The aim of this study was to observe the penetration of an aqueous solution into the root canal dentin under sonic activation and ultrasonic activation. Materials and Method: This study consisted of experimental in vitro research. In order to achieve a closed system, the apex of 45 single-rooted teeth was sealed with wax. The step-back technique was manually performed using a K50 apical master file and 3 groups were organized according to the protocol of the final irrigant activation: Group I: non-activated Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Highest penetration depth in coronal third could be attributed to thelarge and densely packed dentinal tubules seen in the coronal thirdof the root canal followed by middle third, while narrower tubules are located more in the apical thirds, and as a result can limit the ability of irrigant penetration. 34 Both groups demonstrated minimum penetration depth in the apical third of the root canal, this was in agreement with Ghorbanzade et al 16 , Macias et al 35 , and Vandrangi. 36 However, interesting findings was observed in Ultrasonic activation, where the highest penetration depth was in middle third, followed by coronal and apical with no significant differences between the three thirds.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Highest penetration depth in coronal third could be attributed to thelarge and densely packed dentinal tubules seen in the coronal thirdof the root canal followed by middle third, while narrower tubules are located more in the apical thirds, and as a result can limit the ability of irrigant penetration. 34 Both groups demonstrated minimum penetration depth in the apical third of the root canal, this was in agreement with Ghorbanzade et al 16 , Macias et al 35 , and Vandrangi. 36 However, interesting findings was observed in Ultrasonic activation, where the highest penetration depth was in middle third, followed by coronal and apical with no significant differences between the three thirds.…”
supporting
confidence: 85%
“…This finding was in agreement with Vandrangi. 36 Macias et al 35 also showed highest penetration of Chinese ink in the middle third of the root canal when ultrasonic was used.In contrast, Baz et al 37 showed lower penetration depth in middle third than coronal. However, different irrigation protocols were used with up and down motions in activation, while in this study the PUI was set at one position.…”
mentioning
confidence: 96%
“…hypochlorite is the most commonly used irrigant 10,11 as it has most of the aforementioned characteristics, of particular importance is its ability to dissolve organic tissue, which is superior to all the other agents described above. 1,6,12,13 As such, the action of the irrigant has been improved upon by techniques and devices such as laser, sonic, and ultrasonic activation of the irrigating agent; and on the other hand, irrigation protocols have been developed, such as combinations of solutions to be used in a specific sequence during the mechanical and chemical preparation of the canals, in order to achieve a greater degree of removal of microorganisms, organic remains, smear, and thus increase the success rate of root canal therapy.…”
Section: [ E P U B a H E A D O F P R I N T ]mentioning
confidence: 99%